A SURVEY ON TEACHING SPEAKING PERCEPTION EFL LEARNERS’ FLUENCY (A CASE STUDY AT IAIN SYEKH NURJATI CIREBON - Siti Nurhasanah (IAIN Syekh Nurjati Cirebon, 2016)
Abstract : Every human being in the world needs speaking to express their ideas, their feelings and to gain the information. Speaking therefore is very important. Many problems of speaking are faced by EFL Learners of IAIN Syekh Nurjati Cirebon. This research was primarily intended to capture the learners’ speaking fluency level in IAIN Syekh Nurjati Cirebon: the lesson plan reflect the teaching of speaking fluency, how lecturers perceive the concept of speaking fluency, and how the learners’ monitor their speaking fluency. The investigation itself was centered on the conception of the principle of teaching EFL Speaking. To investigate lecturers’ perception of the teaching EFL speaking, the researcher conducted an in-depth interview to speaking and conversation 1 until 5 lecturers. The researcher also analyzed speaking lesson plan as a representation towards lecturers’ orientation in teaching speaking process and also to investigate the level of speaking used by lecturers in teaching speaking and conversation. The researcher also used questionnaire and speaking test as tools to collect data. The analysis process is designed by interpreting the data through transcriptions and analysis. The percentage merely was used to analyze for obtaining descriptive statistics from data collected by in-depth interview and questionnaire. Data from speaking test and document were interpreted and reviewed to get understanding from data collected. The main conclusion of this research are each lecturer has different levels in the learning speaking process and speaking fluency levels determined by lecturer strategies in learning process. Key words: Teaching EFL Speaking, Fluency Levels, Lesson Plan, EFL Learners.